1986
DOI: 10.1161/01.res.59.5.568
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclic flow variations in stenosed canine coronary arteries by thromboxane A2/prostaglandin H2 receptor antagonists.

Abstract: We tested the hypothesis that thromboxane A 2 and thromboxane AJ/PGH2 receptor occupation are important in mediating cyclical reductions in coronary blood flow (CFVs) in concentrically narrowed canine coronary arteries. Two potent and selective thromboxane A2/PGH 2 receptor antagonists, SQ29,548 and SQ28,668 eliminated CFVs and restored a normal pattern of blood flow through the severely narrowed vessels in 77 and 75% of the dogs, respectively. CFVs were eliminated within several minutes of an intravenous bolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Conditioned dogs of both sexes weighing [20][21][22][23][24][25] kg were used in this study. The trisodium salt of aurintricarboxylic acid ( Figure 1) …”
Section: Methodsmentioning
confidence: 99%
“…Conditioned dogs of both sexes weighing [20][21][22][23][24][25] kg were used in this study. The trisodium salt of aurintricarboxylic acid ( Figure 1) …”
Section: Methodsmentioning
confidence: 99%
“…Trial therapy was discontinued for the following reasons: (1) major bleeding defined as transfusion of two or more units of blood, surgical correction, retroperitoneal or intracranial hemorrhage, or bleeding resulting in death or permanent disability, (2) minor bleeding that the study physician believed could not be remediated by adjusting the dose of antithrombotic therapy, (3) development of an end point (recurrent ischemia, myocardial infarction, or death) or of a cerebrovascular accident, (4) if after trial therapy was begun, a patient was found to have normal coronary arteries, nonobstructive coronary artery disease (no lesions .50%), or a negative maximal exercise tolerance test, or there was a clear reason other than progressive ischemic heart disease for the qualifying pain, eg, severe anemia unrecognized at the time of randomization, trial therapy was discontinued; if a patient was determined to have had a transmural infarction as the qualifying event, eg, a true posterior infarction, trial therapy was also discontinued, (5) surgical revascularization or angioplasty, (6) noncompliance with trial medication or missing two consecutive follow-up visits.…”
Section: Withdrawal Of Trial Therapymentioning
confidence: 99%
“…In particular, studies from our laboratory with a canine model of concentrically stenosed and endothelially injured coronary arteries demonstrated the occurrence of a typical cyclic pattern of flow (CFVs) caused by alternating platelet aggregation and subsequent dislodgement of the thrombus and that TXA2 and 5HT are important mediators of CFVs. [17][18][19][20] Blockade of TXA2 usually results in the elimination of CFVs. [17][18][19][20] It is interesting to note that in the present study neither SQ29548 nor LY53857 alone significantly enhanced thrombolysis and prevented CFVs and reocclusion, whereas the combination of the two antagonists was very effective in both enhancing thrombolysis and preventing CFVs and reocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Blockade of TXA2 usually results in the elimination of CFVs. [17][18][19][20] It is interesting to note that in the present study neither SQ29548 nor LY53857 alone significantly enhanced thrombolysis and prevented CFVs and reocclusion, whereas the combination of the two antagonists was very effective in both enhancing thrombolysis and preventing CFVs and reocclusion. This is in contrast with previous studies from our laboratory employing a model of concentrically stenosed and endothelially injured canine coronary arteries17-20 in which either TXA2-or 5HT-receptor blockade usually results in abolition of CFVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation